Fermentation Quality and Additives: A Case of Rice Straw Silage. (27th June 2016) - Oladosu, Yusuff; Rafii, Mohd Y.; Abdullah, Norhani; Magaji, Usman; Hussin, Ghazali; Ramli, Asfaliza; Miah, Gous
Abstract : Rice cultivation generates large amount of crop residues of which only 20% are utilized for industrial and domestic purposes. In most developing countries especially southeast Asia, rice straw is used as part of feeding ingredients for the ruminants. However, due to its low protein content and high level of lignin and silica, there is limitation to its digestibility and nutritional value. To utilize this crop residue judiciously, there is a need for improvement of its nutritive value to promote its utilization through ensiling. Understanding the fundamental principle of ensiling is a prerequisite for successful silage product. Prominent factors influencing quality of silage product include water soluble carbohydrates, natural microbial population, and harvesting conditions of the forage. Additives are used to control the fermentation processes to enhance nutrient recovery and improve silage stability. This review emphasizes some practical aspects of silage processing and the use of additives for improvement of fermentation quality of rice straw.